Low Temperature Preservation and Storage of Placental Biological Derivatives - Prokopyuk, Vladimir Yu.; Falko, Oksana V.; Musatova, Irina B.; Prokopyuk, Olga S.; Royenko, Oleksandr O.; Terekhova, Elena O.; Chub, Oleg V. (Problems of Cryobiology and Cryomedicine, 2015)
The paper covers the actual tasks in low temperature storage of such placental biological derivatives as: cell-free material, cell suspensions, placental tissue, umbilical cord and fetal membranes. Depending on the purposes for biological specimen storage the main research directions in this field are as follows: diagnostic, experimental, clinical, establishment of donor or personal low temperature bank. Nowadays of a top priority is designing the methods for freeze-drying, hypothermic storage, and cryopreservation with different temperature regimens. Probl Cryobiol Cryomed 2015; 25(4):291-311.